Charged poly(N-isopropylacrylamide) nanogels for use as differential protein receptors in a turbidimetric sensor array. Issue 17 (26th July 2017) - Culver, Heidi R.; Sharma, Ishna; Wechsler, Marissa E.; Anslyn, Eric V.; Peppas, Nicholas A.
Abstract : Due to the high cost and environmental instability of antibodies, there is precedent for developing synthetic molecular recognition agents for use in diagnostic sensors. Abstract : Due to the high cost and environmental instability of antibodies, there is precedent for developing synthetic molecular recognition agents for use in diagnostic sensors. While these materials typically have lower specificity than antibodies, their cross-reactivity makes them excellent candidates for use in differential sensing routines. In the current work, we design a set of charge-containing poly( N -isopropylacrylamide) (PNIPAM) nanogels for use as differential protein receptors in a turbidimetric sensor array. Specifically, NIPAM was copolymerized with methacrylic acid and modified via carbodiimide coupling to introduce sulfate, guanidinium, secondary amine, or primary amine groups. Modification of the ionizable groups in the network changed the physicochemical and protein binding properties of the nanogels. For high affinity protein–polymer interactions, turbidity of the nanogel solution increased, while for low affinity interactions minimal change in turbidity was observed. Thus, relative turbidity was used as input for multivariate analysis. Turbidimetric assays were performed in two buffers of different pH ( i.e., 7.4 and 5.5), but comparable ionic strength, in order to improve differentiation. Using both buffers, it was possible to achieve 100% classification accuracy of eleven model protein biomarkers with as few as two of the nanogel receptors. Additionally, it was possible to detect changes in lysozyme concentration in a simulated tear fluid using the turbidimetric sensor array.